Supplementation with inulin-type fructans affects gut microbiota and attenuates some of the cardiometabolic benefits of a plant-based diet in individuals with overweight or obesity - Aldubayan, Mona Adnan; Mao, Xiaotian; Laursen, Martin Frederik; Pigsborg, Kristina; Christensen, Lars H.; Roager, Henrik M.; Nielsen, Dennis S.; Hjorth, Mads Fiil; Magkos, Faidon (Frontiers in Nutrition, 2023)
Background: The gut microbiota has emerged as a potential therapeutic target to improve the management of obesity and its comorbidities. Objective: We investigated the impact of a high fiber (∼38 g/d) plant-based diet, consumed ad libitum, with or without added inulin-type fructans (ITF), on the gut microbiota composition and cardiometabolic outcomes in subjects with obesity. We also tested if baseline Prevotella/Bacteroides ratio predicts weight loss outcomes. Methods: This is a secondary exploratory analysis from the PREVENTOMICS study, in which 100 subjects (82 completers) aged 18-65 years with body mass index 27-40 kg/m2 were randomized to 10 weeks of double-blinded treatment with a personalized or a generic plant-based diet. Changes from baseline to end-of-trial in gut microbiota composition (16S rRNA gene amplicon sequencing), body composition, cardiometabolic health and inflammatory markers were evaluated in the whole cohort (n=82), and also compared in the subgroup of subjects who were supplemented with an additional 20 g/d ITF-prebiotics (n=21) or their controls(n=22). Results: In response to the plant-based diet, all subjects lost weight (-3.2 [95% CI -3.9, -2.5] kg) and experienced significant improvements in body composition (all P < 0.001) and cardiometabolic health indices. Addition of ITF to the plant-based diet reduced microbial diversity (Shannon index) and selectively increased Bifidobacterium and Faecalibacterium (q < 0.05). The change in the latter was significantly associated with higher values of insulin and HOMA-IR and lower HDL cholesterol. In addition, the LDL:HDL ratio, IL-10, MCP-1 and TNFα levels were significantly elevated in the ITF-subgroup. There was no relationship between baseline P/B ratio and changes in body weight (r = -0.07, P = 0.53). Conclusion: A plant-based diet consumed ad libitum has multiple health benefits in individuals with obesity. Addition of ITF-prebiotics on top this naturally fiber-rich background selectively changes gut microbiota composition and attenuates some of the realized cardiometabolic benefits. Clinical trial registry: ClinicalTrials.gov registry NCT04590989 (https://clinicaltrials.gov/ct2/show/NCT04590989).